FAKTOR PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. BENING MATA SANTOSA) - Marsita Wati Anggreini; Endang Masitoh Wahyuningsih; Suhendro Suhendro (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
PT. Bening Mata Santosa is a company engaged in services, namely Event Organizer (EO) and Tour and Travel with a total of 96 employees. In making the company's financial statements, it is necessary to have employee cooperation between interrelated divisions. These include the division of reservations, procurement, marketing, services, social media, tour and travel and accounting. However, the report has not been carried out properly by employees. Due to lack of responsibility, understanding of accounting information systems, weak internal control systems within the company, and lack of understanding of technology.This study aims to determine the factors of the application of accounting information systems on the performance of case study employees at PT Bening Mata Santosa. This type of research is classified as quantitative research. The sample of this study uses purposive sampling method with a total sample of umas (now) so that the total number of questionnaires that will be processed is 60. The data used in this study is primary data, testing in this study uses linear regression analysis multiple. Based on the results of the hypothesis test, it shows that Information System Satisfaction, Internal Control, and the effectiveness of Information System Implementation have an effect on employee performance. While Technology Acceptance has no effect on Employee Performance.Keywords: Implementation SIA and Employee Performance